2002
DOI: 10.1111/1468-2397.00242
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes towards AIDS: a comparison between Arab and Jewish professionals living in Israel

Abstract: This paper investigates similarities and differences between Arab and Jewish professionals living in Israel regarding their knowledge and attitudes about AIDS. Although AIDS in Israel is not considered to be a pressing crisis, the aim of the research is to document and analyse what professionals in the helping professions – Arabs and Jews alike – know and how they feel about AIDS. The study also explores thoughts and feelings concerning AIDS–related education and training. This is the first scholarly attempt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
0
11
1
Order By: Relevance
“…In our study, we found a strong correlation between nurses' level of knowledge and attitudes towards PLHIV. This finding is supported by Azaiza and Ben‐Ari 22 and Walusimbi and Okonsky 20 and is contrary to the findings of Chen and Holzemer 15 …”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…In our study, we found a strong correlation between nurses' level of knowledge and attitudes towards PLHIV. This finding is supported by Azaiza and Ben‐Ari 22 and Walusimbi and Okonsky 20 and is contrary to the findings of Chen and Holzemer 15 …”
Section: Discussionmentioning
confidence: 71%
“…The strongest area of knowledge seems to be modes of HIV transmission, and the weakest HIV pathophysiology 6,7,10,14–20 . Studies made in Nigeria, Iran, China and Israel found almost every nurse to know that HIV can be contracted via blood and sexual intercourse and that normal casual contacts do not increase the risk of infection 10,14,21,22 . There are still nurses who have misconceptions about HIV detection from oral secretion, urine, sweat and tears 10,14,21 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations